Transformative Teaching and Learning Through Engaged Practice: Lecturers' and Students' Experiences in a University and Underserved Community Partnership in Ireland. (July 2019) - Quillinan, Bernie; MacPhail, Ann; Dempsey, Ciara; McEvoy, Eileen
The Community Wellness, Empowerment, Leadership and Lifeskills (CWell) program is a 2-year community-driven program developed in partnership between an underserved community in Limerick City and staff at the University of Limerick, Ireland. This article explores the transformative teaching and learning experiences that arose throughout the duration of the program for the lecturers and students. Data were collected through interviews and focus groups with lecturers and students involved in the program. Students supported the notion of "learning differently" and focused around prior learning and attitude to learning, learning about learning, and impact of learning. Lecturers supported the notion of "teaching differently, " focusing on how they had revised their usual teaching practices to more overtly emphasize the importance of culturally responsive pedagogy and student-centered learning (as opposed to content-centered) and the situated learning perspective. There is a necessity for research on diverse and innovative programs to inform culturally responsive pedagogies and transformation for learning.